Physical training protocols that influence the 5.000m time trial performance: a systematic review - Ferreira Gonçalves, Anderson (2024)
A review of training protocols for the 5.000m race was carried out in order to facilitate the search and comparison between the existing protocols. This study aimed to systematically review the literature on the physical training protocols applied to athletes and well-trained runners who have investigated the impacts on performance in 5,000m races and/or recognised performance parameters in this distance. This review was carried out in accordance with PRISMA guidelines. The search used PubMed, Web of Science and Scopus electronic databases. The PICOS strategy was used to define eligibility criteria. A total of 35 studies were included in the systematic review, 25 studies were selected for qualitative analysis from the databases, and 10 articles were identified during the reading of the articles selected by the main search. Selected studies had their methodological quality and risk of bias assessed by the Cochrane Risk of Bias Tool. Interval running protocols are the main potentiators for performance in the 5.000m. Among all running protocols that improved the 5,000m time trial or any of the predicted variables studied in this review, 33.33% used both interval and continuous training, 33.33% used uphill HIIT, and 13.33% used HIIT. Neuromuscular protocols showed effects mainly on running economy. Eight of the eleven neuromuscular intervention protocols showed improvement in this variable. Among all neuromuscular protocols that improved the 5,000m time trial or any of the predicted variables studied in this review, 50% applied complex training, 25% used plyometric as an intervention and 25% used strength resistance training. The coach must choose the combination of the studied protocols in order to guarantee performance improvement.